ANALISA PERUBAHAN AMANDEMEN UUD 1945 PERUBAHAN PERTAMA TAHUN 1999 SAMPAI PERUBAHAN KE-EMPAT TAHUN 2002 - Wesley Liano Hutasoit (Prodi Ilmu Administrasi Negara, 2018)
The amendment is a formal amendment of an official document or a particular record, especially to remedy it. These changes may include adding or deleting the wrong note, no longer appropriate. This word is generally used to refer to changes in the constitution of a state (constitutional amendment). Constitutional constitutes basic principles of politics and law covering structure, procedure, and authority / rights and obligations. Therefore, the constitution is very closely related to the amendment because it aims to improve a record / important document of a country that covers the form, structure, procedure, to be better than before.The amendments to the 1945 Constitution are: Period 19 October 1999 - August 18, 2000 (1st amendment), Period 18 August 2000 - November 9, 2001 (2nd amendment), Period 9 November 2001 - August 10, 2002 (3rd amendment) , Period August 10, 2002 - until now (4th amendment)